Arginine‐stimulated copeptin in children and adolescents. (5th February 2023) - Binder, Gerhard; Weber, Karin; Peter, Andreas; Schweizer, Roland
Abstract: Objective: Copeptin is secreted in isomolar amounts along with arginine vasopressin peptide (AVP) from the neurohypophysis. Its stability makes it a perfect candidate for the endocrine approach in the diagnosis of AVP deficiency (AVPD; cranial diabetes insipidus; CDI). However, pediatric reference values are lacking. Design and Patients: This is a monocentric retrospective analysis of donated residual serum samples from 72 children and adolescents who underwent arginine or growth hormone‐releasing hormone‐arginine stimulation to test GH secretory capacity from 2018 to 2022. Measurements: Copeptin was measured in baseline, 30‐, and 60‐min samples by BRAHMS Copeptin proAVP Kryptor immunofluorescence assay. Results: Of the 72 patients, 4 suffered from complete AVPD (CDI). The baseline level of copeptin in the 68 non‐AVPD (non‐CDI) patients was highly variable (range: 1.3–44.4 pmol/L). The increase after arginine was moderate (30 min range: 1.6–40.4 pmol/L). The median baseline and peak copeptin levels were 5.6 and 8.0 pmol/L, respectively. The 2.5th percentile of the baseline and peak values of copeptin were 2.1 and 3.3 pmol/L, respectively. The increase and peak value of copeptin were inversely related to age ( R  = −.405; p  = .011, and R  = −.335; p  = .0072, respectively) but not to gender, body mass index (standard deviation score) or GH secretion. In the four patients with AVPD (CDI), baseline or stimulated copeptin was below the 2.5th percentile of non‐AVPD (non‐CDI) patients. Conclusions: Stimulated copeptin is a promising parameter for the differential diagnosis of polyuria‐polydipsia syndrome. However, the low copeptin increase after arginine and the high limit of quantification of the assay are problematic for use in paediatrics.